Semiotic Interpretation of Bangla Ligatures: An Introduction - Afrin, Sanjida (Dhaka University Journal of Linguistics, 2010)
Semiotics is the study of sign processes emphasizing signification and communication, signs and symbols of different social phenomena. In the late 19th and early 20th century the works of Ferdinand de Saussure and Charles Sanders Peirce led to the emergence of semiotics as a separate discipline as well as method for examining phenomena in different fields, including aesthetics, anthropology, communications, psychology, and semantics. Saussure's interpretation of linguistic sign from a semiotic perspective has, better or worse, affected much of subsequent discussions about language. But according to Peirce, meaning is not directly attached to the sign; instead, it is mediated through the interaction between the representamen, interpretant, and object. This paper initiates a brief semiotic interpretation of Bengali ligature-an essential component of Bengali writing system, since semiotics considers ligature, like other linguistic components, a potential sign-unit. Key words: ligature, Saussure, Peirce, Object. DOI: 10.3329/dujl.v2i3.4147 The Dhaka University Journal of Linguistics: Vol.2 No.3 February, 2009 Page: 111-124